O imposto sobre grandes fortunas : reflexões acerca dos limites ao poder de tributar do Estado e o dever fundamental de pagar tributos - Figueiredo, Laura de Oliveira Mello (2019)
The aim of this research is to explore the Wealth Tax and its possibility of implementation in Brazil, through the analysis of theories of justice, tax payer’s fundamental rights and the fundamental duty of paying taxes. To do so, we investigate the contributions given by John Rawls, Robert Nozick and Adam Smith to taxation theory, seeking for a fiscal justice conception to sustain taxation in modern democracies. In sequence we approach the fundamental rights of the tax payer that should sustain taxation in Brazil’s constitutional tax system, and analyse the fundamental duty to pay taxes, understood as a duty of preserving colectivity, sustained by law and respecting the taxpayer’s fundamental rights. At the end we investigate the Wealth Tax in Brazil’s legal system, providing international data in order to illustrate the scenario of the its attemptives of implementation, the brazilian complementary law projects that have been presented so far and the possibility of providing extra fiscal effects to the tax imposition. Finally, we appreciate the wealth tax in the context of the theories of justice and tax payer’s fundamental rights. The approach method is the deductive hypothetical, since we propose the hypothesis that the wealth tax does not attend to justice and fundamental rights criteria. The procedural methods are the structuralist and the functionalist, considering we aim to approach the theme not from conceptual point of view alone, but considering its social applications. The comparative method is applied not in totality, but as a clarifying instrument. The interpretation methods are the systematic and sociological, aiming to study the wealth tax in the context of the brazilian tax system, its limitations to the power to tax and the fundamental duty of paying taxes. The conclusion is aligned with the premise that taxation should be restrained by a concept of justice, and sustained by ability to pay, the certainty of tax imposition, always maintaining the most of the tax payer's patrimony. Fundamental rights are instruments for the protection of the tax payer, being the State's duty to aim for solutions that are closer to its citizens. The wealth tax does not fulfil the effectivity required by the constitution, since it is sustained in the belief that it should act as an instrument of property and individual initiative limitation, which is not admitted by Brazil's constitutional order.